Síntese de novos diésteres derivados da piperina como potenciais candidatos a agentes antimicrobianos e antitumorais - Trindade, Emmely Oliveira da (2021)
Black pepper (Piper nigrum L.) is the most consumed spice in the world, being a fruit of great economic and pharmaceutical importance. The beneficial physiological effects of black pepper, such as: relief of pain and chills, treatment of colds and flu, rheumatism, among others, are attributed to its main active ingredient, piperine. This, in turn, has a wide spectrum of biological activities and has been playing an important role as a raw material for the synthesis of new compounds with pharmacological interest. The objective of this research was the use of piperine, extracted from black pepper, as a precursor in the synthesis of new derived molecules, in order to evaluate the antimicrobial and antitumor potential of these compounds. Initially, two series of substituted chloro-esters and the salt of piperic acid were planned and synthesized as intermediates, which were submitted to a nucleophilic bimolecular substitution reaction (SN2) giving rise to 30 new diesters derived from piperine. The final compounds showed yields between 50 and 84% and were characterized by infrared (IR) spectroscopic techniques, 1H and 13C nuclear magnetic resonance (NMR) and 2D NMR (COSY, HSQC, HMBC). The biological potential of the final compounds were evaluated through the in silico study, in vitro antimicrobial activity, acute non-clinical toxicity and in vivo antitumor activity. In the in silico study, only the compounds Butyl 4-(4-iodobenzoate)- piperate (DE-05) and Butyl 4-(3,5-dinitrobenzoate)-piperate (DE-08) violated two of the Lipinski parameters, therefore, it can be inferred that the other compounds must present a good oral bioavailability. In the in vitro antimicrobial evaluation, bacterial strains (Staphylococcus aureus and Pseudomonas aeruginosa), yeast fungi (Candida albicans and C. tropicalis) and filamentous fungi (Aspergillus fumigatus, A. flavus and A. niger) were used. The result of the evaluation of the final compounds showed that the substance Butyl 4-(4- methylbenzoate)-piperate (DE-06) presented a more comprehensive antimicrobial action, managing to inhibit several strains with a minimum inhibitory concentration (MIC) of 256 µg/ml. Most of all substances were effective against yeast fungi, and only a small portion of these substances were also effective against filamentous fungi. However, none of the final products had antibacterial activity. The compound 4-(4-nitro-benzoate)-butyl piperate (DE 07) was submitted to acute non-clinical toxicity tests, the lethal dose (LD50) was estimated at 1000 mg/kg, being considered a low compound acute toxicity. The result of the evaluation of the in vivo antitumor effect of the compound DE-07, in an Ehrlich ascitic carcinoma (EAC) model, showed a significant reduction in the tumor mass and in the parameters of viability and total cell; such results allow us to infer that the compound, in the experimental model evaluated, has significant antitumor activity in vivo.